2022
DOI: 10.1021/acssuschemeng.2c01339
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment of Corn Stover by Levulinic Acid-Based Protic Ionic Liquids for Enhanced Enzymatic Hydrolysis

Abstract: Economically competitive and sustainable dissolution pretreatment technology is in high demand due to the remarkable achievement in the pretreatment of lignocellulose using ionic liquids (ILs) for enhanced enzymatic hydrolysis. Herein, levulinic acid (Lev), a well-known bio-based platform chemical derived from carbohydrates, in conjunction with a series of organic superbases, was used as a raw chemical to prepare a new class of protic ILs (PILs). The findings indicated that the obtained PILs exhibited a good s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…S7-S10, † indicating a clear reaction between lignin and DHC or the epoxides individually under identical conditions. 31 P NMR was identified as a powerful tool to evaluate the various types of hydroxyl groups distributed in lignin, 49 which will provide direct evidence of the two initiating process shown in Scheme 1, as both will result in the transformation of different types of hydroxyl groups (Fig. S11 †).…”
Section: Synthesis and Characterization Of Ehl-g-p(dhc-alt-epo)mentioning
confidence: 96%
See 2 more Smart Citations
“…S7-S10, † indicating a clear reaction between lignin and DHC or the epoxides individually under identical conditions. 31 P NMR was identified as a powerful tool to evaluate the various types of hydroxyl groups distributed in lignin, 49 which will provide direct evidence of the two initiating process shown in Scheme 1, as both will result in the transformation of different types of hydroxyl groups (Fig. S11 †).…”
Section: Synthesis and Characterization Of Ehl-g-p(dhc-alt-epo)mentioning
confidence: 96%
“…Details of the tests are shown in ESI Text S1. † 49 The total degree of polymerization (DP) of DHC and SO alternating copolymer fragments was determined with eqn (1) according to a previous publication: 39…”
Section: Measurements and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, various researches have been conducted on the decomposition of different types of lignocelluloses by the protic ILs. For instance, Chen et al suggested to fractionate corn stover by [DBNH][Lev], and a reducing sugars yield of 0.80 g g −1 pulp was obtained [ 18 ]. Semerci et al analyzed the capacities of various proton ionic liquids to the fractionation of lignocelluloses, among which, the highest glucose yield of 92% was obtained using [TEA][HSO 4 ] [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lignocellulosic biomass is considered as the most abundant source of renewable carbon on Earth, with an estimated annual production of 2·10 11 tons, mainly represented by residues from forestry and agriculture [ 1 ]. Given its nature as a renewable resource, lignocellulosic biomass is considered as a promising alternative to fossil sources to obtain chemicals [ 2 , 3 , 4 ] and biofuels [ 5 , 6 ]. Through an acid-catalyzed dehydration process, it is possible to convert the carbohydrate component of biomass (cellulose, hemicellulose, and related subunits such as glucose, xylose, galactose, arabinose, etc.)…”
Section: Introductionmentioning
confidence: 99%